effect of adding of sabah snake grass (clinacanthus nutans) on the antioxidant and sensory properties of chocolate : Additional of sabah snake grass on chocolate quality - Mansoor Abdul Hamid; Kai Yen Lim; Chi Hong Yeap; Mazarina Devi; Maryana Muhamad Nor (POLTEKKES KEMENKES MEDAN, 2023)
This research was carried out to identify the effect of drying methods on the antioxidant activity of Sabah snake grass leaves as well as the addition of Sabah snake grass powder on the antioxidant and sensory properties of chocolate. Antioxidant properties of chocolate samples were determined through total phenolic content and DPPH radical scavenging activity tests. The best formulation of chocolate filled with Sabah snake grass was determined based on sensory and antioxidant test. Nutrient content of chocolate was determined through AOAC methods whereas water activity and hardness of chocolate shell were determined using water activity meter and Texture Analyzer. Changes of chocolate during storage was reviewed through the aspect of moisture content, water activity, hardness, melting point, microorganism count and sensory score. Results showed that chocolate F2, chocolate filled with 100g of Sabah snake grass powder was the best formulation with satisfaction by panels and higher antioxidant activity. This sample contain 7.25% moisture, 2.19% ash, 30.61% fat, 5.41% protein, 1.94% crude fibre and 52.61% carbohydrate. The storage sample showed significantly difference (p<0.05) in moisture content, water activity, hardness and melting property after kept for eight weeks but still safe to be consumed.